Pembangunan Desa Pasca Undang-Undang No. 6 Tahun 2014 tentang Desa [Village Development Post Law No. 6 of 2014 on Villages] - Lindawaty, Debora Sanur (Jurnal Politica, 2023)
The village government is one of the institutions that has an important role in equitable distribution of development and prosperity in Indonesia. Seeing the importance of the village's role in realizing development and welfare, the central government made a law that recognized village autonomy authority, namely Law No. 6 of 2014 concerning Villages (Village Law). This law gives the widest possible rights to villages to manage their own territory. This paper will examine village development after Law No. 6 of 2014 concerning Villages. Development, especially in terms of building democracy at the village level as well as developing infrastructure and the village economy. It was found that in terms of village development, the Ministry of Villages has established several indicators that make it easy for villages to find out how far the level of village independence is. This instrument is known as the Development Village Index (IDM). Meanwhile, to become an advanced and independent village, there are several programs and innovations that can be developed by the village. Village independence and democracy are tools to achieve the welfare of the Village people. Both pave the way for the village to have the right to manage natural resources or allocate funds for improving basic services and developing the local economy. Some things that need to be done in optimizing village development according to the Village Law are continuing to strengthen village democracy through the level of community participation, increasing village IDM, and being able to create competitive products.AbstrakPemerintah desa merupakan salah satu lembaga yang memiliki peran penting dalam pemerataan pembangunan dan kesejahteraan di Indonesia. Melihat pentingnya peran desa dalam mewujudkan pembangunan serta kesejahteraan, pemerintah pusat membuat undang-undang yang mengakui kewenangan otonomi desa yaitu UU no 6 Tahun 2014 tentang Desa (UU Desa). Undang-Undang ini memberikan hak seluas-luasnya pada desa untuk mengatur wilayahnya sendiri. Tulisan ini akan mengkaji tentang pembangunan desa pasca Undang-Undang No 6 Tahun 2014 Tentang Desa. Pembangunan terutama dalam hal pembangunan demokrasi di tingkat desa maupun pembangunan infrastruktur dan ekonomi desa. Ditemukan bahwa dalam hal pembangunan desa, Kemendes telah menetapkan beberapa indikator yang memberi kemudahan kepada desa untuk mengetahui sejauh mana tingkat kemandirian desa. Instrumen tersebut dikenal dengan istilah Indeks Desa Membangun (IDM). Sedangkan untuk menjadi desa maju dan mandiri ada beberapa program dan invovasi yang dapat dikembangkan desa. Kemandirian dan demokrasi Desa merupakan alat untuk mencapai kesejahteraan rakyat Desa. Keduanya membuka jalan bahwa desa berhak untuk mengelola sumberdaya alam atau alokasi dana bagi perbaikan pelayanan dasar dan pengembangan ekonomi lokal. Beberapa hal yang perlu dilakukan dalam optimalisasi pembangunan desa sesuai UU Desa ialah terus memperkuat demokrasi desa melalui tingkat partisipasi masyarakat, meningkatkan IDM desa, serta mampu menciptakan produk yang berdaya saing.